The Effectiveness Of Role-Play In Improving Grade Seven Students’ English Speaking Skills at SMP N 3 Tareran - Sinaga, Mei Elita Sari; Rorimpandey, Rinny S; Wongkar, Yapi (Program Studi Pendidikan Bahasa Inggris, 2025)
Speaking is one of the essential skills in learning a language, as it plays a crucial role in effective communication. However, many students face challenges in developing their speaking skills, such as lack of confidence, limited vocabulary, and insufficient opportunities for practice. As a result, researchers and educators are increasingly using role-play method as a tool for teaching foreign language. The purpose of this study is to investigate the effectiveness of the role-play method in improving students’ speaking skill. This study was delimited on the teaching speaking skills using role-play method at the seven grade of SMP Negeri 3 Tareran. This study was conducted using quantitative method. Furthermore, the design of this study was pre-experimental with one group pretest dan posttest, which consisted 16 students were the subject of this study. The result of this study showed that the mean score in the posttest was higher (80.44) than mean score of pretest (50.19). Based on the result, it can be concluded that the use of role-play can improve students’ speaking skills.